Elites instruidas en la Costa Rica colonial, 1564-1718 - Madrigal Muñoz, Eduardo (2008)
By means of a prosopographic study and using a social networks theoretical approach, this article explores the social functions of knowledge, as well as its ways of transmission in the Costarican colonial society. A documented presentation of the main traits of the evolution of the formal education in the period is also offered. As a result, the work concludes that knowledge was in the hands of a very narrow social network structured with very well connected individuals, who were also rich and politically powerful. These individuals used their position and their monopoly of knowledge to impede access to it to other social groups of the time, using it, at the same time, as a tool to sustain their social position.